Metabolic dysfunction-associated steatotic liver disease as a predictor of cognitive performance: an 11-year population-based follow-up study - Vataja, Emilia (My University, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD), formerly non-alcoholic fatty liver disease, is a prevalent liver manifestation of metabolic dysfunction. MASLD has been shown to be associated with poorer cognitive performance and cognitive decline. Possible mechanisms for this association are, for example, insulin resistance of the brain, lipotoxicity, low-grade inflammation derived from excess adipose tissue and inflamed liver, and sustained hyperglycemia disrupting the blood-brain barrier. However, explaining the association is difficult since risk factors for cognitive dysfunction and MASLD are similar in nature, and etiology of cognitive dysfunction is multifactorial in nature. In this study, we examined the effect of MASLD at baseline on cognitive decline during a follow-up period of 11 years. We defined MASLD as Fatty Liver Index (FLI) value over 60. The FLI considers waist circumference, body-mass index, serum triglycerides and serum gamma-glutamyl transferase concentrations, and it has been widely used in epidemiological research to define MASLD. The main finding in our study was that having MASLD at baseline predisposes to cognitive decline over time. This was shown by decline in performance in the word-list learning test after the follow-up period of 11 years. We also showed that by adjusting for metabolic and cardiovascular covariates, the significance of MASLD decreases highlighting the importance of metabolic aspect of this liver disease. These findings underline the importance of treating MASLD as it affects millions of people worldwide and has an effect on cognitive functions. Still, more research is needed to validate these results and to determine mechanistic pathways via which MASLD causes cognitive dysfunction.
Keywords: MASLD, NAFLD, cognitive dysfunction, cognitive decline